MODEL MULTILITERASI DALAM PERKULIAHAN PENDIDIKAN BAHASA DAN SASTRA INDONESIA - Esti Swatika Sari (Faculty of Languages and Arts, Universitas Negeri Yogyakarta, 2013)
This study aims to describe a model of literacy in the Indonesian Language and Literacy Education course. It employed the qualitative descriptive method involving three subjects, namely Dialectical Speaking, Syntopical, Creative, and Critical Reading, and Discourse Analysis. The data were collected through a questionnaire for lecturers, interviews with students, student assignment documents, learning materials, and lecturers’ evaluation system. The findings are as follows. First, in Dialectical Speaking, the multiliteracy competencies developed are linguistic, gestural, and spatial competencies. Second, in Syntopical, Creative, and Critical Reading, they are linguistics, visual, audiovisual, and spatial competencies. Third, in Discourse analysis, they are linguistics, spatial, and visual competencies. Multiliteracy in a course can also be viewed from the practice situation, open learning, critical thinking reflection, and transformative practice.